Tear lactoferrin and ceruloplasmin levels in patients with traumatic and recurrent corneal erosions - Iryna Gavrylyak; Dmytro Zhaboiedov; Dmytro Zhaboiedov; Artem Tykhomyrov (Ukrainian Society of Ophthalmologists, 2024)
Background: Studies on the mechanisms of corneal wound healing are still important. Apart from the integrity of the corneal epithelium, tear fluid is important for maintaining homeostasis of the ocular surface; it is composed of a variety of proteins, lipids and metabolites. Studies on changes in concentrations of biochemical tear components are important for the diagnosis and treatment of corneal injuries. Purpose: To assess changes in tear lactoferrin (Lf) and ceruloplasmin (Cp) levels over the course of comprehensive treatment for patients with traumatic corneal erosions (TCE) and recurrent corneal erosions (RCE). Material and Methods: The study sample included 62 patients (19 to 65 years of age; mean age plus or minus standard deviation, 43.5 ± 2.4 years). Group 1 included 44 patients with TCE, and group 2, 18 patients with recurrent RCE. Each patient group was divided into two subgroups on the basis of the treatment method. Subgroup 1 was administered eye broad-spectrum antibiotic (AB) eye drops and dexpantenol over a course of treatment. Subgroup 2 received AB eye drops and dexpantenol plus adjunct lactoferrin (Lf)-containing eye drops. An eye examination included visual acuity, biomicroscopy and fluorescein test. Monospecific antibodies were used to determine tear Lf and Cp levels. Tears from healthy volunteers were used as controls. Results: At baseline, the tear Lf level in patients with TCR was lower than in controls (3.94 ± 0.45 arbitrary units (a.u.) versus 10.3 ± 0.4 a.u., respectively; p < 0.05), resulting in reduced ocular surface protection. In subgroup 1 of the TCE group, after treatment with an AB plus dexpantenol only, the tear Lf level increased to 6.38 ± 0.55 a.u. (p < 0.05), and the mean period of treatment was 7.6 ± 0.43 days (p ≥ 0.1). In subgroup 2 of the TCE group, after treatment with an AB plus dexpantenol plus Lf-containing eye drops, the tear Lf level was 12.23 ± 0.6 a.u. (p < 0.05) and the mean period of treatment was 6.0 ± 0.23 days. The presence of Cp in the tear fluid prior to treatment for TCE or RCE indicated activation of acute inflammation; at baseline, the tear Cp level in patients with TCE was 2.37 ± 0.25 a.u. compared to controls (p < 0.05), and in those with RCE, 1.78 ± 0.2 a.u. On completion of treatment with Lf-containing eye drops, the tear Lf level increased and the tear Cp level decreased to the levels in controls, and there was a negative correlation between the tear Lf level and the tear Cp level (r = -0.491, p < 0.001). Conclusion: The results confirmed the feasibility of utlizing Lf-containing eye drops as an adjunct in the treatment of TCE and RCE. This approach contributed to the restoration of ocular surface homeostasis, thus promoting corneal epithelialization and enabling a reduction in treatment duration.